A Reflection on the Gendered Implications of What Kinship Is - Alessandra Gribaldo (Antropologia)
This article proposes a reflection on kinship starting from a recent debate between Marshall Sahlins and Warren Shapiro hosted by the Journal of the Royal Anthropological Institute, between 2011 and 2012. The heated controversy about the “new kinship studies”, regarding sense, meaning, and ultimately the nature of human relatedness, finds the two anthropologists on divergent stances: on one hand kinship as mutuality of being, a locus for multiple ways to conceive and live relatedness, on the other kinship as biological and inescapable invariant of human relations. The article aims at highlighting how some key issues related to relations of power remain undertheorised in the “beyond constructivist” and “essentialist” views deployed in the Sahlins-Shapiro contention and underlines the ways that kinship issues engage with broad political stances. Finally, I introduce a reflection on gender as a possibly crucial, and yet eluded, dimension in the debate.